Respiratory Health Risk Assessment of Deforestation in Kalimantan: Analysis of PM2.5 Exposure in Local Communities in Forest Fire Areas - Megawati; Vevi Endriani; Risnawati Tanjung; Aulia Zikra; Aulia Rahmi Cheni (Knowledge and Environmental Science for Living and Global Health, 2025)
This study evaluated the association between exposure to fine particulate matter (PM2.5) due to deforestation and forest fires and the risk of respiratory disorders in local communities in Kalimantan, Indonesia. A mixed-methods design with an observational epidemiological approach was used to evaluate the impact of exposure to PM2.5 on acute respiratory infections (ARI), asthma exacerbations, and community lung function. A cross-sectional survey was conducted to assess the prevalence of respiratory diseases and socioeconomic factors influencing exposure levels. Field measurements of PM2.5 both indoors and outdoors were used to estimate population exposure based on time-activity and indoor/outdoor ratios. Results showed that outdoor workers had an average exposure of 156.3 g/m3-hour, significantly higher than indoor workers, and this difference was significant (p  0.001). Indoor workers had a mean exposure of 88.5 l/hr, and the difference was statistically significant. The regression model showed that every 10 m3 increase in PM2.5 increased the odds of ARI by 11% (OR=1.11, 95%CI: 1.06-1.17). This study emphasizes the importance of strengthening the air quality monitoring system, health early warning, and stricter land use regulations to improve community resilience to future recurring haze events.